2021
DOI: 10.9734/ijecc/2021/v11i1230586
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Yield and Yield Attributing Traits in Advanced Breeding Lines of Rice (Oryza sativa L.)

Abstract: Aim: Present study endeavors to explore the genetic variability for various agro-morphological and quality traits as well as to delineate the association between grain yield and its yield attributing components Study Design: Randomized Complete Block Design Place and Duration of Study: Division of Plant Breeding and Genetics, She-e-Kashmir University of Agricultural Sciences and Technology of Jammu during kharif 2020. Methodology: A experiment was carried out to determine the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…The findings of present study confirmed that characters 1000 grain weight, plant height, days to 50 per cent flowering and grain yield per plant were found to have high genetic advance (GAM) coupled with high heritability implying that these traits efficiently inherited from generation to generation. Sandeep et al [11], Mushtaq et al [12] and Choudhary et al [9] also reported similar results in their respective studies. Yield being polygenic control (Table 3) can not be selected directly as it is influenced by cumulative action of genes with unknown effects.…”
Section: Resultssupporting
confidence: 59%
“…The findings of present study confirmed that characters 1000 grain weight, plant height, days to 50 per cent flowering and grain yield per plant were found to have high genetic advance (GAM) coupled with high heritability implying that these traits efficiently inherited from generation to generation. Sandeep et al [11], Mushtaq et al [12] and Choudhary et al [9] also reported similar results in their respective studies. Yield being polygenic control (Table 3) can not be selected directly as it is influenced by cumulative action of genes with unknown effects.…”
Section: Resultssupporting
confidence: 59%